The Role of Mindfulness Parenting in Supporting Early Childhood Emotional Development - Maryana; Rismaida P. A. Napitupulu (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study examines the role of mindful parenting in supporting the emotional development of early childhood. Emotional regulation problems among young children, such as tantrums and behavioral difficulties, are often associated with less responsive parenting practices. Therefore, this study aims to analyze how parenting mindfulness contributes to children's emotional development and to identify the mechanisms underlying this relationship. This research employed a quantitative approach with a cross-sectional survey design involving 245 parents of children aged 3–6 years. Data were collected using standardized instruments, including the Interpersonal Mindfulness in Parenting Scale (IM-P), Emotion Regulation Checklist (ERC), and Parent–Child Relationship Scale (PCRS). The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that mindful parenting has a significant positive effect on children's emotional development. Parents with higher levels of mindfulness tend to demonstrate greater emotional awareness, non-reactivity, and responsiveness, which foster a supportive emotional environment for children. Furthermore, the findings reveal that the parent–child relationship and parental emotion regulation significantly mediate this relationship. Children of mindful parents show better emotional regulation, with an improvement of approximately 18% compared to those with lower levels of mindful parenting. In conclusion, mindful parenting plays a crucial role in enhancing early childhood emotional development through improved parental emotional regulation and stronger parent–child relationships. This study highlights the importance of integrating mindful parenting practices into parenting education and early childhood programs.